PEMBERDAYAAN KELOMPOK TANI DESA SIMORO DALAM MENGATASI KELEBIHAN PRODUKSI LABU SIAM MELALUI PEMBUATAN PANGAN FUNGSIONAL UNTUK ANAK STUNTING - Sakung, Jamaludin M.; Lukman, Lukman; Rahman, Abd.; Dewi, Nikmah Utami (Jurnal Abdi Insani, 2024)
The "Bukit Indah" farmer group in Simoro village is an economically/socially productive partner group, because no solution has been implemented to overcome overproduction of chayote. The potential waste from chayote is in the form of fruit waste. This waste is very abundant and most of it is left to rot. The decomposition of this waste causes an unpleasant odor and in the long term will reduce environmental quality. The aim of this service is for the team and partners to collaborate in processing chayote which exceeds production into functional food for under-five and stunted children. Implementation Method: Conduct surveys and identify farmer groups that have the potential to be involved in this program. Establishing partnerships with farmer groups who are willing to participate, the farmer group that has the potential to become a partner is the "Bukit Indah" farmer group in Simoro village. The results of the activity obtained understanding of farmer groups and female cadres in processing agricultural products into food with nutritional value and becoming an innovation in handling the problem of stunting children, increasing cadres' skills in processing chayote into food products, and processing it themselves with the materials provided and intervening with children target toddlers, the intervention was carried out for 20 days with administration 2 days apart, and after the intervention, the average weight and height of the toddlers before the intervention were 10,275  kg and 78,7  cm respectively and after the intervention it was 10,845  kg and 78,951  cm. Training on innovation of food products from chayote in community service activities can overcome stunting and provide solutions to malnutrition among under-aged children.